PERTIMBANGAN HAKIM DALAM MEMUTUSKAN PERKARA TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN (Studi Putusan Nomor : 130/Pid.B/2025/PN.Tjk) I - Sesly Deno Putri; Baharudin Baharudin; Risti Dwi Ramasari (Peneliti.net, 2026)
The crime of aggravated theft is a form of crime against property that is still frequently occurring in society and requires firm handling through the criminal justice process. This study aims to analyze the judge's considerations in deciding the case as stated in Decision Number: 130/Pid.B/2025/PN.Tjk. The judge's considerations in passing the verdict have been based on the fulfillment of the elements of the crime as regulated in Article 363 paragraph (2). This decision reflects the application of retributive punishment theory, namely the imposition of punishment as a consequence of a criminal act that has been consciously committed by the defendant. Data collection through library research and field research. The research method used is normative legal research with a statutory approach and a case approach, through the study of court decisions, as well as relevant legal literature. Data sources are obtained from court decisions accompanied by data collection conducted through research and interviews to obtain information and also answers to the main issues studied.